The Interest Rate Sensitivity of Investment - Guido Baldi; Alexander Lange (Credit and Capital Markets, 2019)
The interest rate sensitivity of investment has often played an important role in macroeconomic models. However, many vector autoregressive (VAR) models do not include investment to the list of variables. In this paper, we empirically investigate the size and the evolution of the interest rate sensitivity of investment for the United States and the four largest European economies in the last few decades. We use a VAR model with four variables at quarterly frequency: real investment, real gross domestic product (GDP), inflation, and a measure of the short-term interest rate. In our VAR, the structural interest rate shock is identified under the assumption that macroeconomic quantities and inflation react to interest rate innovations with a lag. We test the appropriateness of this specification by comparing our approach with the identification of shocks derived from the changes in volatility approach. For the countries under consideration, we determine a date during either the 1980s or the 1990s where the interest rate sensitivity of investment began to decrease and became less responsive to monetary policy. In addition, we find that the interest rate sensitivity of investment has been higher in the United States than in Europe, particularly in the first subperiod.
Keywords: E22; E43; E52; 330; Investment; Monetary Policy; Effect of Interest Rates